Orientation-dependent energy-storage performance and electrocaloric effect in PLZST antiferroelectric thick films - Zhao, Ye; Gao, Hongcheng; Hao, Xihong; Zhang, Qi (Elsevier, 2016)
The enhancement of the energy-storage performance and electrocaloric effect (ECE) was achieved via orientation control. The 1.5-μm-(Pb0.97La0.02)(Zr0.73Sn0.22Ti0.05)O3 (PLZST) antiferroelectric (AFE) thick films with (111), (110), and (100) crystallographic orientations were successfully prepared via a sol-gel method. It was found that both the enhanced energy-storage density of 13.5 J/cm3 at 900 kV/cm and the corresponding temperature reduction of ΔT = 28.1 °C at room temperature were obtained in the PLZST thick film with (111) orientation due to a high polarization. Moreover, these films with different orientations display a small leakage current density at the room temperature. These results suggest that both energy-storage properties and cooling performance in AFEs could be optimized by the proper orientation control.